Socio-Economic and Demographic Factors Associated With Enhancing Reproductive Health of Women in Bunyafa Sub County Sironko District - Morren Namuhenge (Uganda Christian University, 2024)
Background: many women do not have access to reproductive health leading to high morbidity and high child mortality Objective: this aimed at assessing social -economic and Demographic factors associated with enhancing reproductive health of women in Bunyafa sub county sironko Method: the study used cross sectional study with the help of both qualitative and quantitative approaches. Data was collected from 80respondents in Bunyafa sub county using a structured questionnaire and interview guide. Purpossive sampling technique was used to select research participants. Quantitative data was analysed using descriptive statics and content analysis for qualitative data. Results: the findings of research study show that limited decision making(39 percent) hinder access to reproductive health services by women alongside gender roles (29percent). In addition socio-demographic factors of age(36 percent) and place of residence(rural or urban) (45 percent) determines Access to reproductive health of women. Further soco economic factors such as income levels (42percent), peer influence (53 percent) and levels of women's education have been cited as central determinants of access to reproductive health of women. Conclusion: young women without decision making power and residing in rural areas with low income and low education levels have been found to have less or no access to reproductive health. Recommendation: the ministry of health together with gender, labour and social development counterpart should strengthen enforcement of policies regarding universal access to reproductive health by women, curtail social exclusion and improve availability, accessibility and utilization of reproductive health by women. Also the government should reduce taxation on entrepreneural businesses so as to boost economic household income through business incubation, Skilling an parish development model for the empowerment of marginalized and economically unsound person including women groups.